Design and Simulation of Automatic Ballast System on Catamaran Ship Based on Programmable Logic Control - Indra Ranu Kusuma (International Journal of Marine Engineering Innovation and Research, 2017)
Characteristics of catamaran ship which has deficiency to ship stability during maneuvering. to that end, this paper concerns about ballast system design in support of the safety and comfort of passengers on the catamaran boat. the discussion is done by creating a mathematical model of each component in the block diagram of the ballast system. then determine the pid value of the system and add the compensator for the system to run stable. further analyzed with the help of matlab software to get transient system response. with the automation system on the ballast system, it is expected that the motion of the ship can work automatically and provide a better response in the stability of the catamaran type ship. the ballast system begins to work against the tilt of the ship at 6.7 seconds at a certain angle, and will continue to work during the vessel maneuvering. judging from the 6.7 second system response time, the convenience of the passengers is not disturbed (the system response is not too fast). one way to reduce the rolling that occurs on the ship is to optimize the performance of the ballast system. performance optimization is done by using programmable logic controller (plc). plc used is omron cpm1a-30cdr-a-v1. the process is done by making the installation plant model of the ballast system as a control medium. followed by creating a control circuit consisting of wiring i / o, limit switch circuits, power supplies and programming languages associated with plcs. the result of the control is expected to regulate fluid flow in the ballast system automatically resulting in a rapid response to the stability of the ship.